A puerperal haemorrhagic state due to a heparin-like anticoagulant - Willoughby, M. L. N. (1963)
The occurrence of a severe generalized haemorrhagic state in an obstetric case due to a heparin-like anticoagulant is described. This appeared in the post-partum period apparently following a compatible blood transfusion. The pattern of results found in conventional laboratory tests for elucidating acute blood coagulation disorders is described, and the distinction between heparinaemia and the defibrination syndrome emphasized. Protamine sulphate corrected the clotting abnormality in vitro and when administered in amounts so as to achieve a similar concentration in vivo was followed by correction of the blood coagulation and the sudden cessation of bleeding from multiple sites.